Construct validity of Paulhus’ Comprehensive Inventory of Desirable Responding (CIDR) - Parmač Kovačić, Maja (Array, 2008)
The aim of this study was to test the metric characteristics of the Croatian version of Paulhus’ Comprehensive Inventory of Desirable Responding (2006). The CIDR comprises four subscales intended to measure components of social desirability: agentic management, agentic enhancement, communal management and communal enhancement. For this purpose independent samples of participants were tested in three situations with different instructions for self-presentation: one honest (N1=224) and two different “ fake good” instructions (N2=249, N3=196). The data showed that reliability, sensitivity and discriminant validity of the instrument were satisfactory. However, conducted factor analyses only partially confirmed the model. Further studies are needed.